Percepções e sentimentos de estudantes na avaliação em educação física escolar - Rogério Alves Antunes Júnior (2020)
The present work discusses students' perceptions and feelings when they are evaluated by different instruments: written test, sports performance, portfolio and self-assessment. To start the discussion, we made a historical review of the evaluation in general and specifically in school Physical Education. Nineteen students of the seventh year participated in the research. We used as a tool for collecting data, a quis with discursive questions that was applied after the use of each evaluative instrument. The results point to the need of expanding the use of evaluation instruments, but at the same time understand that the use of them does not guarantee an improvement in teaching if they are not aligned with the concept of evaluation as a means and not an end. This work did not intend to rank the evaluation instruments, even because it would not be possible, however, we believe in the word “possibility” in the sense that we will never find the ideal evaluation model, but on the possibility of approaching it.